MODIFICATION OF ADSORBEN SILICA FROM RICE HUSK ASH WITH CHITOSAN TO ADSORPTION ION MANGANESE (TOTAL) - Fauzi, Akhmad; -, Alimuddin; Widodo, Nanang Tri (Jurusan Kimia FMIPA UNMUL, 2020)
Adsorbent silica from rice husk ash supported by chitosan can be used to adsorb Mn (Total) metal. The adsorbent is regulated by adjusting the composition of 65% silica and 35% chitosan. The characteristics of the silica-chitosan adsorbent and the adsorbent interaction with Mn (Total) are believed to be based on Fourier Transform Infared (FTIR) data. The concentration of Mn (Total) ion after adsorption is determined by Atomic Absorption Spectrophotometer (AAS). The results showed optimum pH at pH 5 percentage adsorption 79.45% and optimum contact time at 60 minutes with adsorption percentage 96.78%, and obtained chitosan-silica adsorption capacity of Mn (Total) ions of 1.0349 mg/g.